Research on the Ethical Governance Model of Stem Cells Technology - Huiyu LUO; Bingqian WANG (Yixue yu zhexue, 2025)
China's regulation of the stem cell field has closely followed global trends, evolving through a binary opposition between "loose" and "strict" regulatory frameworks. However, as clinical stem cell research continues to yield substantial evidence, with growing therapeutic success and increasing demand-supply imbalance, it is imperative to reassess the tension and balance between these two models. This calls for the establishment of basing on reflective equilibrium ethical governance model for the stem cells field. This model advocates for comprehensive communication and dialogue among researchers, policymakers, and the public. It emphasizes achieving a more holistic and adaptive governance consensus by seeking maximal harmony and coherence between ethical judgments, moral principles, and relevant contextual theories. The ultimate goal is to meet the demands of scientific advancement and public needs, thereby facilitating the healthy and sustainable development of stem cells technologies.